Oxide-Based Nanocomposites for Food Packaging Application: A Review - Aisha Idris Ali; Munir Abba Dandago; Fatima Idris Ali; Genitha Immanuel; Jishnu Naskar (University of Sultan Ageng Tirtayasa, 2022)
Silver nanoparticles and/or nanoclay [particularly montmorillonite] are used in the majority of nanotechnology applications for food packaging. Other nanomaterials, on the other hand, can also be integrated into packaging. Metal oxide nanoparticles have been added to petroleum-based and biopolymers to produce nanocomposites with improved mechanical, barrier, antioxidants and antimicrobial properties. Nanoparticles migration from packaging, on the other hand, is a source of concern due to their potential toxicity in the human body and the environment. The purpose of this article therefore, was to review the available literature on the utilization of metal oxide-based nanoparticles to produce nanocomposites for food packaging application. Advantages of incorporating metal oxide-based nanoparticles into polymers, as well as migration of these nanomaterials from packaging into foods are discussed. Incorporation of metal oxide nanoparticles into polymers allows for the production of nanocomposites with increased mechanical strength, water and oxygen barrier properties, and can also confer other additional functional properties, such as antioxidant, antimicrobial activity and light-blocking properties. According to migration studies, only a small quantity of nanomaterial migrates from packaging into food simulants or foods, implying that consumer exposure to these nanomaterials and the health concerns associated with them are low. Nonetheless, there is a scarcity of information on the migration of nanomaterials from packaging into actual foods, and more research is desperately needed in this area. This manuscript is useful in the food industries as it indicate the applicability and potential of the oxide-based nanocomposites as a promising approach for use in food packaging applications.